A Review on Abrasive Flow Machining (AFM). (2016) - Kumar, S. Santhosh; Hiremath, Somashekhar S.
Abstract: The required finish/texture is one of the prime requirements in various, finished components through conventional machining, processes like grinding, lapping, polishing and super finishing processes. Industries are spending huge amount of money to get the required finish and texture after the components being machined. This will calls for advanced non conventional finishing processes. Abrasive Flow Machining (AFM) is one of the non conventional finishing processes in which a semi-solid medium consisting of a visco-elastic polymer and abrasive particles mixed in a definite proportion. This media is extruded under pressure through or across the surface to get the required finish. In this article an attempt has been made to review various published technical papers on AFM and segregated into four categories - experimental setups, abrasive media, modeling and optimization and applications. The review paper opens new research avenues for further work.